Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3324/haematol.2019.238147
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-specific novel long non-coding RNA and circular RNA in the BLUEPRINT hematopoietic transcriptomes atlas

Abstract: Transcriptional profiling of hematopoietic cell subpopulations has helped characterize the developmental stages of the hematopoietic system and the molecular bases of malignant and non-malignant blood diseases for the past three decades. Previously, only the genes targeted by expression microarrays could be profiled genome wide. High-throughput RNA sequencing (RNA-seq), however, encompasses a broader repertoire of RNA molecules, without restriction to previously annotated genes. We analysed the BLUEPRINT conso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
1
10
0
1
Order By: Relevance
“…In consequence, the comparison between unadjusted and adjusted models for cellular composition can provide information about potential cell type-specific eQTMs. Our results seem to support our hypothesis, as eQTMs exclusive to the main unadjusted model, and thus potential cell type-specific, were composed by CpGs and TC with higher cell type specificity (higher F-statistic) in blood cell methylation and expression sorted studies [30,31]. Of note, a high F-statistic can either mean high methylation/expression differences in one particular blood cell type or intermediate methylation/expression differences across several cell types.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In consequence, the comparison between unadjusted and adjusted models for cellular composition can provide information about potential cell type-specific eQTMs. Our results seem to support our hypothesis, as eQTMs exclusive to the main unadjusted model, and thus potential cell type-specific, were composed by CpGs and TC with higher cell type specificity (higher F-statistic) in blood cell methylation and expression sorted studies [30,31]. Of note, a high F-statistic can either mean high methylation/expression differences in one particular blood cell type or intermediate methylation/expression differences across several cell types.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, we checked our hypothesis that CpGs and TCs in eQTMs uniquely identified in the main model (unadjusted cell-specific eQTMs) are blood cell type-specific by contrasting them with data from sorted blood cell types. For this, we retrieved DNA methylation levels from six sorted blood cell types by Reinius and colleagues [30] and gene expression levels from twelve sorted blood cell types from the Blueprint project [31]. We used the log 10 of the F-statistic of a linear regression (see Material and Methods) as a measure of cell type specificity (higher F-statistic, higher specificity), as described elsewhere [32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, cathelicidin antimicrobial peptide (Camp), cysteine-rich secretory protein 3 (Crisp3), and neutrophil gelatinase-associated lipocalin (Lcn2) were all differentially less abundant in GPS neutrophils, and all localize to the neutrophilspecific granules. 45 Cross-referencing the discriminatory plasma proteins with the BLUEPRINT consortium gene expression data 51 revealed that 14 of the discriminatory plasma proteins are not known to be expressed in hematopoietic cells (Figure 4B; supplemental Figure 4). We then analyzed the gene expression of these 14 proteins in the Genotype-Tissue Expression database, 52,53 which showed that 9 of these nonhematopoietic proteins are predominantly synthesized by liver-residing cells.…”
Section: The Gps Plasma Proteome Has a Proinflammatory And Hepatic Signaturementioning
confidence: 99%